Tax compliance on business income as applied to hawkers in Section 2, Shah Alam, Selangor Darul Ehsan / Sofiah Othman - Othman, Sofiah (1993)
The degree of tax compliance on business income has always been questionable despite abundant efforts taken by the Tax Authorities to improve it. Realising upon this fact, the writer decided to carry out a study to gauge the degree of tax compliance on business income within a specified scope i.e on the hawkers in Section 2, Shah Alam, Selangor. The collection of data was made via personal interviews, distribution of questionnaires as well as direct observations on a few selected occasions which are of weekdays, weekends and semester holidays. Evaluation was made based on the intensity of variance between the amount of tax payable as per writer's computation ( based on information gained which is subject to the limitations) and the amount of tax claimed to be paid by these hawkers. The result shows that there is a poor degree of compliance and it is seen to be a necessity for certain measures to be enforced without hesitation in order to maximise voluntary compliance among the hawkers.